Insight into Phosphatidylinositol-Dependent Membrane Localization of the Innate Immune Adaptor Protein Toll/Interleukin 1 Receptor Domain-Containing Adaptor Protein - Patra, Mahesh Chandra; Choi, Sangdun (Frontiers in Immunology, 2018)
The Toll-interleukin 1 receptor (TIR) domain-containing adaptor protein (TIRAP) plays an important role in the Toll-like receptor (TLR) 2, TLR4, TLR7, and TLR9 signaling pathways. TIRAP anchors to phosphatidylinositol (PI) 4,5-bisphosphate (PIP2) on the plasma membrane and PI (3,4,5)-trisphosphate (PIP3) on the endosomal membrane and assists in recruitment of the myeloid differentiation primary response 88 protein to activated TLRs. To date, the structure and mechanism of TIRAP’s membrane association are only partially understood. Here, we modeled an all-residue TIRAP dimer using homology modeling, threading, and protein-protein docking strategies. Molecular dynamics simulations revealed that PIP2 creates a stable microdomain in a dipalmitoylphosphatidylcholine bilayer, providing TIRAP with its physiologically relevant orientation. Computed binding free energy values suggest that the affinity of phosphatidylinositol (PI)-binding domain (PBD) for PIP2 is stronger than that of TIRAP as a whole for PIP2, and that the short PI-binding motif (PBM) contributes to the affinity between PBD and PIP2. Four PIP2 molecules can be accommodated by distinct lysine-rich surfaces on the dimeric PBM. Along with the known PI-binding residues (K15, K16, K31, and K32), additional positively charged residues (K34, K35, and R36) showed strong affinity toward PIP2. Lysine-to-alanine mutations at the PI-binding residues abolished TIRAP’s affinity for PIP2; however, K34, K35, and R36 consistently interacted with PIP2 headgroups through hydrogen bond (H-bond) and electrostatic interactions. TIRAP exhibited a PIP2-analogous intermolecular contact and binding affinity towards PIP3, aided by a H-bond network involving K34, K35, and R36. The present study extends our understanding of TIRAP’s membrane association, which could be helpful in designing peptide decoys to block TLR2-, TLR4-, TLR7, and TLR9-mediated autoimmune diseases.